-2(-3m-7)=24-4m

Simple and best practice solution for -2(-3m-7)=24-4m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(-3m-7)=24-4m equation:


Simplifying
-2(-3m + -7) = 24 + -4m

Reorder the terms:
-2(-7 + -3m) = 24 + -4m
(-7 * -2 + -3m * -2) = 24 + -4m
(14 + 6m) = 24 + -4m

Solving
14 + 6m = 24 + -4m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '4m' to each side of the equation.
14 + 6m + 4m = 24 + -4m + 4m

Combine like terms: 6m + 4m = 10m
14 + 10m = 24 + -4m + 4m

Combine like terms: -4m + 4m = 0
14 + 10m = 24 + 0
14 + 10m = 24

Add '-14' to each side of the equation.
14 + -14 + 10m = 24 + -14

Combine like terms: 14 + -14 = 0
0 + 10m = 24 + -14
10m = 24 + -14

Combine like terms: 24 + -14 = 10
10m = 10

Divide each side by '10'.
m = 1

Simplifying
m = 1

See similar equations:

| -11=2x-3+2x | | 4x+12=2x+3 | | 125.(4/3) | | .5(x-28)=12+7x | | x+x(.28)=2.87 | | 4[7x-45]=9 | | 0=2v+5v | | 5x-3/y=4x | | -3x^2+500=1000 | | 50+3x=6(-x+6)-58 | | 3log(12-4x)=9 | | 8x^2-100=700 | | 27+a=7(-4a+8) | | -8+3u=-20 | | 20a-13a-21=0 | | -5(2x-9)=2(x-7)-13 | | d(t)=1/3t-12 | | 19+2.50x=11+3.75x | | 3x-3=45-9x | | 9-3p=8p | | 3/2p-2=-7/9 | | 31-4r=-7(-4a+8) | | 3x^2+90=190-7x | | 2x+-5=12 | | 354=35t+.5*9.8*t^2 | | -24n^2=36n | | 2m^2+4=6m | | -2v-2v=-7(1+6r) | | 27=2m+5 | | Z^2+12Z-45=0 | | 20x6/14x2 | | 2m+37=67 |

Equations solver categories